Safety performance in a lean environment a guide to building safety into a process - English, Paul F. (CRC Press, 2011)
"Foreword For some people, the combination of lean enterprise and environmental health and safety (EHS) is like mixing oil and water. The reality is that both have many commonalities. In many cases, people focus on lean as only for the manufacturing floor and their processes, but that couldn't be further from the truth. Lean is about behavioral change: a change for the better, identifying simple and waste-free methods to perform any activity, process, or service. In EHS, approximately 85% of all injuries are related to poor behaviors (unsafe acts); therefore we must create a safety culture. EHS professionals must recognize the power of the lean culture and use its power to build upon their own EHS culture. Why not incorporate EHS into the idea of standardized work for all activities, why not incorporate safety into your 5S audits, why not visualize safety within the visual management tools in the workplace, why not make safety part of leadership standard audits and shop floor (Gemba) walks, and why not work with your lean leadership to change the culture together? EHS already has many of the expected lean tools in its arsenal. When an injury occurs, it is expected that the EHS and leadership team react quickly with a sense of urgency to solve the root cause of the injury. Therefore, we all rush to the area to see what happened (go and see), we investigate and utilize problem-solving techniques (5-Why, 8D, etc.). We do our best to find and eliminate the root cause of that injury and we look for other areas or similar conditions and implement corrective actions (yokoten or knowledge sharing). From my 18 years of lean experience, that sure does sound like a strong lean culture and methodology"-- Provided by publisher.
Keywords: Industrial safety.; Lean manufacturing.; Environmental health.; elektronické knihy; electronic books